Menimbang Komunikasi Spiritual: Sebuah Tinjauan Konseptual - Putut Widjanarko (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Paramadina, 2022)
The discourse on the relationship between religion and spirituality with communication studies has attracted the interest of many researchers, including Indonesian researchers. However, the literature produced by Indonesian researchers on the discourse, including those that investigate the relationship of communication and Islam, appear to be detached from the wider context. Therefore, the purpose of this article is to provide a more theoretical background to this discourse. The conceptual review method is applied to enable the researcher to explore the literature and develop conceptual maps to produce theoretical syntheses, develop new theories, or encourage attention to areas of study that have been underdeveloped so far. This article emphasizes the development of the Spiritual Tradition in communication studies and describes the dialogical and dialectical junctures with other communication theory traditions in Craig's (1997, 2007) metamodel. With such a theoretical background, the discourse on the study of communication and Islam in Indonesia can be directed to more contextual studies that is related to a wider discourse.